Monte Carlo as quality control tool of stereotactic body radiation therapy treatment plans. (April 2021) - Alhamada, Husein; Simon, Stephane; Gulyban, Akos; Gastelblum, Pauline; Pauly, Nicolas; VanGestel, Dirk; Reynaert, Nick
Highlights: A Monte Carlo model of linear accelerator head was created and Validated. Dosimetry comparisons of MC with Monaco treatment planning system were done for 40 SBRT patients of various cancer types. Proof the visibility of using Monte Carlo as a quality control tool of the patient's dosimetry. Abstract: Purpose/objective: The objective of this study was to verify the accuracy of treatment plans of stereotactic body radiation therapy (SBRT) and to verify the feasibility of the use of Monte Carlo (MC) as quality control (QC) on a daily basis. Material/methods: Using EGSnrc, a MC model of Agility™ linear accelerator was created. Various measurements (Percentage depth dose (PDD), Profiles and Output factors) were done for different fields sizes from 1x1 up to 40x40 (cm 2 ). An iterative model optimization was performed to achieve adequate parameters of MC simulation. 40 SBRT patient's dosimetry plans were calculated by Monaco™ 3.1.1. CT images, RT-STRUCT and RT-PLAN files from Monaco™ being used as input for Moderato MC code. Finally, dose volume histogram (DVH) and paired t-tests for each contour were used for dosimetry comparison of the Monaco™ and MC. Results: Validation of MC model was successful, as <2% difference comparing to measurements for all field's sizes. The main energy of electron source incident on the target was 5.8 MeV, and the full width at half maximum (FWHM) of Gaussian electron source were 0.09 and 0.2 (cm) in X and Y directions, respectively. For 40 treatment plan comparisons, the minimum absolute difference of mean dose of planning treatment planning (PTV) was 0.1% while the maximum was 6.3%. The minimum absolute difference of Max dose of PTV was 0.2% while the maximum was 8.1%. Conclusion: SBRT treatment plans of Monaco agreed with MC results. It possible to use MC for treatment plans verifications as independent QC tool.